2008
DOI: 10.1080/09651560802604989
|View full text |Cite
|
Sign up to set email alerts
|

Migrants and the Unequal Burdening of “Toxic” Risk: Towards a New Global Governance Regime

Abstract: This is an electronic version of an article published in:Charles Woolfson and Branka Likic-Brboric, Migrants and the unequal burdening of "toxic" risk: Towards a new global governance regime, 2008, Debatte, (16) AbstractThe article addresses the changing discourse that frames the neo-liberal regulatory agenda, in the context of the current financial crisis and related, system-threatening 'toxic' risk. In this, the authors claim that a flexible mix of regulation/deregulation and self-regulation is reflected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
1
11
0
2
Order By: Relevance
“…As the global recession started, Woolfson and Likic-Brboric (2008) suggested that these migrants are carrying an unequal burden of 'toxic' risk, in terms of both precarity and dangerous working conditions.…”
Section: Recent Migration: a Solution To Euro-sclerosis?mentioning
confidence: 99%
“…As the global recession started, Woolfson and Likic-Brboric (2008) suggested that these migrants are carrying an unequal burden of 'toxic' risk, in terms of both precarity and dangerous working conditions.…”
Section: Recent Migration: a Solution To Euro-sclerosis?mentioning
confidence: 99%
“…This would have the effect of facilitating companies operating in accordance with the rules and regulations in their home country, generating profound implications to industrial relation standards and the European Social Model (Woolfson and Sommers, 2006;Woolfson et al, 2010). In addition to this development, further impacts on the bargaining positions of workers -especially migrants in precarious employment -have been highlighted against the background of global economic downturn which has exposed labour to an increased 'unequal risk-burdening' (Woolfson and Likić-Brborić, 2008;Woolfson, 2010). These recent changes to a formally well-regulated labour market model in Sweden have particularly impacted low-wage occupations and created new areas for migrant precariousness.…”
Section: Anti-discrimination and Trade Unions In Times Of Transitionmentioning
confidence: 99%
“…Undocumented workers may thereby be forced to go deeper underground in order to avoid authorities and remain undetected (Stark, 2007;Sager 2011). Avoidance of, or complete withdrawal from, the public sphere additionally contribute to the unequal power relation between employer and employee; as these workers keep low profiles it is possible for the employer to neglect health and safety regulations and ultimately force the employees to endure unsafe practices and hazardous working environments (Ahmad, 2008;Woolfson and Likić-Brborić, 2008). All of these discrepancies from conventional labour market relations also become challenges to the work conducted by trade unions.…”
Section: Undocumented Migrant Workers and Channels Of Supportmentioning
confidence: 99%
“…Precarity is a term that in political economy has come to denote unstable employment, the erosion of social protection and general vulnerability in living and working conditions as a general norm (Schierup, Munck, Brboric-Likic, & Neergaard, 2015;Woolfson & Likic, 2008). The term seems particularly appropriate to describe conditions in colonial Southern Africa, where labour and regional movement rights were already actively denied and labour protections blatantly absent.…”
Section: Precarious Labourmentioning
confidence: 99%
“…Socially constructed by the regulatory norms that govern both citizenship and international movement (Woolfson & Likic, 2008), migrant irregularity is reflective of particular regimes of social organisation and movement that marginalise those who do not conform to this normative framework. As hinted above, in the Southern African case, the logic of colonial borders, although still applicable to state territoriality, orients waged labour towards the management of racial categories, first through the designation of labour reserves, labour compounds, 'group areas' and presently through cross-border movement, access to employment and the management of labour frontiers.…”
Section: Migrationmentioning
confidence: 99%